\(\sqrt{x+2}+2x+10=\sqrt{2x-3}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
https://coccoc.com/search?query=%E2%88%9B%28x-20%29%2B%E2%88%9A%28x%2B15%29%3D7
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Ta có:
\(B=\sqrt{1-6x+9x^2}-3x\)
\(B=\sqrt{\left(1-3x\right)^2}-3x\)
\(B=\left|1-3x\right|-3x\)
Nếu \(x>\frac{1}{3}\) thì \(B=3x-1-3x=-1\)
Nếu \(x\le\frac{1}{3}\) thì \(B=1-3x-3x=1-6x\)
b) Xét ta thấy x = 0,5 > 1/3 nên khi đó: B = -1
Nếu x = 0: \(B=1-6\cdot0=1\)
Nếu x = -0,5: \(B=1-6\cdot\left(-0,5\right)=4\)
c) Ta có: \(B>2\)
\(\Leftrightarrow1-6x>2\)
\(\Leftrightarrow-1>6x\)
\(\Rightarrow x< -\frac{1}{6}\)
a) \(B=\sqrt{1-6x+9x^2}-3x\)
\(=\sqrt{\left(1-3x\right)^2}-3x\)
\(=\left|1-3x\right|-3x\)
Với x ≤ 1/3 => B = 1 - 3x - 3x = 1 - 6x
Với x > 1/3 => B = 3x - 1 - 3x = -1
b) Với x = -0, 5 < 1/3 => B = 1 - 6.(-0,5) = 4
Với x = 0 < 1/3 => B = 1 - 6.0 = 1
Với x = 0, 5 > 1/3 => B = -1
c) Để B > 2
=> | 1 - 3x | - 3x > 2 (*)
Với x ≤ 1/3
(*) ⇔ 1 - 3x - 3x > 2
⇔ -6x > 1
⇔ x < -1/6 ( tm )
Với x > 1/3
(*) ⇔ 3x - 1 - 3x > 2
⇔ -1 > 2 ( vô lí )
Vậy x < -1/6
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Ta có:
\(A=2x+\sqrt{x^2-6x+9}\)
\(A=2x+\sqrt{\left(x-3\right)^2}\)
\(A=2x+\left|x-3\right|\)
Nếu \(x< 3\) thì: \(A=2x+3-x=x+3\)
Nếu \(x\ge3\) thì: \(A=2x+x-3=3x-3\)
b) Ta có: \(\left|x\right|=5\Leftrightarrow\orbr{\begin{cases}x=5\\x=-5\end{cases}}\)
Nếu x = 5: \(A=3\cdot5-3=12\)
Nếu x = -5: \(A=-5+3=-2\)
c) Ta có: \(A=2\Leftrightarrow\orbr{\begin{cases}x+3=2\\3x-3=2\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=-1\\x=\frac{5}{3}\left(ktm\right)\end{cases}}\)
Vậy x = -1
a) \(A=2x+\sqrt{x^2-6x+9}\)
\(=2x+\sqrt{\left(x-3\right)^2}\)
\(=2x+\left|x-3\right|\)
Với x ≥ 3 => A = 2x + x - 3 = 3x - 3
Với x < 3 => A = 2x + 3 - x = x + 3
b) | x | = 5 => x = ±5
Với x = 5 > 3 => A = 3.5 - 3 = 12
Với x = -5 < 3 => A = -5 + 3 = -2
c) A = 2
⇔ 2x + | x - 3 | = 2
⇔ | x - 3 | = 2 - 2x (*)
Với x ≥ 3
(*) ⇔ x - 3 = 2 - 2x
⇔ x + 3x = 2 + 3
⇔ 4x = 5
⇔ x = 5/4 ( ktm )
Với x < 3
(*) ⇔ 3 - x = 2 - 2x
⇔ -x + 2x = 2 - 3
⇔ x = -1 ( tm )
Vậy x = -1